Health and population in South Asia from earliest times to the present - Guha, Sumit (New Delhi Permanent Black, 2001)
The history of human population is of special interest when human being are aware of the burden they place on ecosystem. Asia has long contained a major fraction of world populationThis book highlights debates on the population history of Asia, Europe and
Keywords: Health-South Asia-History; South Asia-Population